1997
DOI: 10.1073/pnas.94.18.9973
|View full text |Cite
|
Sign up to set email alerts
|

F-actin and G-actin binding are uncoupled by mutation of conserved tyrosine residues in maize actin depolymerizing factor (ZmADF)

Abstract: Actin depolymerizing factors (ADF) are stimulus responsive actin cytoskeleton modulating proteins. They bind both monomeric actin (G-actin) and filamentous actin (F-actin) and, under certain conditions, F-actin binding is followed by filament severing. In this paper, using mutant maize ADF3 proteins, we demonstrate that the maize ADF3 binding of F-actin can be spatially distinguished from that of G-actin. One mutant, zmadf3-1, in which Tyr-103 and Ala-104 (equivalent to destrin Tyr-117 and Ala-118) have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…The basic residues found in b-sheet 4, b-sheet 5, a-helix 3, and a-helix 4 are conserved in several ADF/cofilin genes and are important for F-actin binding activity (Jiang et al, 1997;Lappalainen and Drubin, 1997;Pope et al, 2000;. According to published reports, b-sheets 4 and 5 and a-helix 4 of ADF are in spatial proximity to one another and likely form an essential F-actin binding surface (F-surface 1) with a relatively high level of conservation of key basic residues (Lys-86, Lys-88, and Arg-141) ( Figure 5A) (Lappalainen and Drubin, 1997;Bowman et al, 2000;Pope et al, 2000).…”
Section: Several Crucial Sites Are Responsible For the Divergent Biocmentioning
confidence: 99%
“…The basic residues found in b-sheet 4, b-sheet 5, a-helix 3, and a-helix 4 are conserved in several ADF/cofilin genes and are important for F-actin binding activity (Jiang et al, 1997;Lappalainen and Drubin, 1997;Pope et al, 2000;. According to published reports, b-sheets 4 and 5 and a-helix 4 of ADF are in spatial proximity to one another and likely form an essential F-actin binding surface (F-surface 1) with a relatively high level of conservation of key basic residues (Lys-86, Lys-88, and Arg-141) ( Figure 5A) (Lappalainen and Drubin, 1997;Bowman et al, 2000;Pope et al, 2000).…”
Section: Several Crucial Sites Are Responsible For the Divergent Biocmentioning
confidence: 99%
“…Two regions have been implicated in filament binding as follows: (i) a cluster of charged residues (15,27) in a loop connecting ␤2 and ␤3 in destrin and at a similar position at the beginning of ␤5 in yeast cofilin, and (ii) a group of charged residues in helix ␣4 in yeast cofilin (27). In addition, mutations of conserved tyrosine residues (Tyr 67 and Tyr 70 in maize ADF3) in the apolar core of the molecule results in uncoupling of monomer and filament binding activities (37).…”
Section: Actin Depolymerizing Factor (Adf)mentioning
confidence: 99%
“…The cofilin-actin interface has been investigated by a number of methods including chemical cross-linking (19,(55)(56)(57)(58), competition with other ABPs (24, 59 -63), structural prediction analysis (63), and mutagenesis (64,65). The consensus of these studies is that subdomain 1 of actin is the principal actinbinding interface that binds the long helix of the ADF-cofilin.…”
Section: Involvement Of Actin Subdomain 1 In the Interaction Withmentioning
confidence: 99%
“…These authors suggested that one of these sites bound one actin monomer within a filament, whereas the second site bound a second actin monomer. Another mutagenic study (64) suggests the importance of the "long helix" (␣3) stability in binding F-actin, but not G-actin.…”
Section: Involvement Of Actin Subdomain 1 In the Interaction Withmentioning
confidence: 99%